Enhancing Program Outcome Mapping and Attainment through Integrated Educational Activities - Beldar, Pankaj; Kushare, Prashant; Shelar, Mahesh; Joshi, Ajinkya (Journal of Engineering Education Transformations, 2026)
This study investigates the influence of integrating diverse educational interventions, including open-ended assignments, expert talks, interdisciplinary workshops and industrial visits, on Program Outcome (PO) mapping and attainment in engineering education. Utilizing past data, the research assesses the efficacy of these initiatives in enhancing student learning experiences and outcomes within the Outcome-Based Education (OBE) framework. Open-ended assignments are examined as mechanisms for cultivating critical thinking and problem-solving skills, while expert talks serve as avenues for bridging theoretical knowledge with real-world applications. Furthermore, interdisciplinary workshops and industrial visits are scrutinized for their contributions to hands-on learning, industry exposure, and teamwork development. The study incorporates two case studies to elucidate the impact of these interventions on PO mapping and attainment, providing valuable insights for curriculum design and educational practice in engineering education. Notably, the analysis reveals that Batch 2 exhibits commendable attainment, underscoring the effectiveness of integrated educational approaches in fostering student success.